Fabrication, mechanical properties and damping capacity of shape memory alloy NiTi fiber-reinforced metal–intermetallic–laminate (SMAFR-MIL) composite. (5th April 2016) - Wang, Enhao; Guo, Chunhuan; Zhou, Peijun; Lin, Chunfa; Han, Xiaoxiao; Jiang, Fengchun
Abstract: A novel Shape Memory Alloy NiTi fiber-reinforced metal-intermetallic–laminate (SMAFR-MIL) composite with a volume fraction of 3.5% NiTi was fabricated using vacuum hot pressing method in this paper. The microstructure characterization of this laminate composite was performed by scanning electron microscope (SEM), energy dispersive spectrometer (EDS) and X-ray diffractometer (XRD), and the mechanical property of SMAFR-MIL composite was determined by compression test. In addition, damping capacity was measured using Dynamic Mechanical Analyzer (DMA) in a temperature range from 30 °C to 50 °C. The experimental results indicated that the average compressive strength and the strain to failure are 1208 MPa and 4.4% for loading perpendicular to the layers, and 962 MPa and 4.8% for loading parallel to the layers, respectively. The loss modulus of SMAFR-MIL composite is 3.7 GPa, which is five times greater than that of Ti/Al3 Ti laminate composite without NiTi fiber reinforcement, while the damping factor of SMAFR-MIL composite is 4.5%. Both the mechanical and damping tests demonstrated that SMAFR-MIL composite is a new class of structural and functional composite with superior mechanical and damping properties. Graphical abstract: Highlights: A new class of NiTi fiber-reinforced laminate composite is designed and synthesized. The interface of NiTi fiber and matrix is metallurgically bonded well. Mechanical and damping properties are determined by compressive test and dynamic mechanical analyzer. Damping mechanisms of fiber-reinforced laminate composite are proposed and analyzed.